CONCOMITANT USE OF CORTICOSTEROIDS AT THE BASELINE DOES NOT AFFECT THE DRUG SURVIVAL OF ABATACEPT IN RHEUMATOID ARTHRITIS - Koca, S. S.; Oz, B.; Karatas, A.; Dalkilic, H. E.; Can, G.; Pehlivan, Y.; Onen, F. (Bmj Publishing Group, 2018)
[Abstract Not Available]
Congress of the European-League-Against-Rheumatism (EULAR) -- JUN 13-16, 2018 -- Amsterdam, NETHERLANDS